2017
DOI: 10.1038/gim.2016.223
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive outcomes and age of detection of severe mucopolysaccharidosis type 1

Abstract: The US Secretary of Health and Human Services recommended in February 2016 that mucopolysaccharidosis type 1 (MPS I) be added to the recommended uniform screening panel for state newborn screening programs. One of the key factors in this decision was the evidence suggesting that earlier treatment with hematopoietic cell transplantation (HCT) for the most severe form, Hurler syndrome (MPS IH), would lead to improved cognitive outcomes. Consistent evidence from peer-reviewed studies suggests that transplantation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 27 publications
0
23
1
Order By: Relevance
“…Previous studies revealed that although affected newborns usually do not clearly exhibit signs of the disease, an elevation of GAGs can be measured in human fetuses and placentas [9], suggesting that the disease can be detected before the first clinical manifestations occur. Considering the irreversible nature of organ damages in MPS patients, experts have agreed that an early initiation of treatment may lead to significant delay and/or prevent the onset of clinical signs and improved outcomes [6,[10][11][12][13][14][15]. Therefore, it has been recommended that newborns be screened for MPSs in the hopes of identifying them early.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies revealed that although affected newborns usually do not clearly exhibit signs of the disease, an elevation of GAGs can be measured in human fetuses and placentas [9], suggesting that the disease can be detected before the first clinical manifestations occur. Considering the irreversible nature of organ damages in MPS patients, experts have agreed that an early initiation of treatment may lead to significant delay and/or prevent the onset of clinical signs and improved outcomes [6,[10][11][12][13][14][15]. Therefore, it has been recommended that newborns be screened for MPSs in the hopes of identifying them early.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has been recommended that newborns be screened for MPSs in the hopes of identifying them early. Moreover, MPS I was added in 2015 to the Recommended Uniform Screening Panel for the United States [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of mucopolysaccharidosis type I (MPS I) into newborn screening in the United States and internationally has been driven by an ever-growing body of evidence that early treatment leads to more favorable outcomes 1 . Early treatment inhibits the generally irreversible, progressive pathology of MPS I, and thus newborn screening affords greater numbers of patients better opportunity for reducing or preventing cognitive or physical disability.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, his neurocognitive trajectory has not aligned with age‐level expectations, and therefore his scores are all generally lower. This pattern of lower post‐UCBT performance even after an intact pre‐UCBT baseline is seen in other neuropathic IMD such as Hurler syndrome and cerebral adrenoleukodystrophy (Aldenhoven et al, ; Coletti et al, ; Grosse, Lam, Wiggins, & Kemper, ; Pierpont et al, ; Shapiro et al, ). Longer term examination of neurocognitive function in other IMD post‐HCT suggests stabilization of neurocognition, provided that intervention occurred early enough in the disease process.…”
Section: Resultsmentioning
confidence: 85%
“…Longer term examination of neurocognitive function in other IMD post‐HCT suggests stabilization of neurocognition, provided that intervention occurred early enough in the disease process. Given the progressive nature of these conditions, earlier treatment is associated with better neurocognitive outcomes, as disease burden is interrupted prior to a severe level of accumulation and neurocognitive damage(Aldenhoven et al, ; Grosse et al, ; Muenzer, Wraith, Clarke, & International Consensus Panel on Management and Treatment of Mucopolysaccharidosis I, ; Pierpont et al, ; Poe, Chagnon, & Escolar, ; Shapiro et al, ). As this is the first report of UCBT for β‐mannosidosis, it will be critical to pursue further follow‐up in this child to determine if he continues to acquire neurocognitive skills, versus a developmental stagnation or actual skill loss.…”
Section: Resultsmentioning
confidence: 99%